PENGARUH LATIHAN STANDING BARBELL TRICEPS EXTENSION TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA PERMAINAN BOLA VOLI TIM PUTRA TRI WIJAYA DIESEL PEKANBARU - Zakia, Nur; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is that the strength of service still lacking, it is seen from various test and official match and this is one factor causing the defeat. This type of research is a type of experimental research to see the effect of the form of exercise. The population in this study is the team tri wijaya diesel pekanbaru, amounting to 12 people. Sampling technique is by using total sampling, where the total population is sampled. The purpose of this study is to see the effect of training standing barbell triceps extension against the strength of arm and shoulder muscle on volley ball game team putra of tri wijaya diesel pekanbaru. The data retrieval technique is obtained from pre-test and post test. Instrument in this research use test expanding dynamometer to measure the muscle of arm and shoulder strength skill to service. The analysis was performed using the t-test. Based on data analysis and discussion, it can be concluded that there is a significant influence of training standing barbell triceps extension against the the strength of arm and shoulder muscle on volley ball game of team putra of tri wijaya diesel pekanbaru proven with Thitung of 9.3 and Ttabel 1.782. Means Thitung> Tables. At É‘ = 0,05 level.Keywords: training standing barbell triceps extension, muscle of arm and shoulder strength